The Earliest History of the Constellations in the Near East and the Motif of the Lion-Bull Combat - Hartner, Willy
I. The Problem; II. The Theory; III. The Sphere of the Fixed Stars in 4000 B.C.; IV. Conjunction versus Heliacal Rising; V. The Ancient Calendars; VI. Conditions for First and Last Visibility; VII. The Constellation of the Bull (Taurus) and the Pleiades; VIII. Aquarius, the Ibex, the Mouflon and the Stag; the Eagle and the Sacred Tree; IX. The Motifs of the Sumerian Gaming-board. The Constellation of the Goat (uza, enzu); X. The Symbol in the Horns of the Ibex and Mouflon, and the Constellation 1-ikû; XI. The Accuracy Test; XII. The Lion-Bull and the Lion-Stag Combats.